2011
DOI: 10.1007/s00404-011-1858-1
|View full text |Cite
|
Sign up to set email alerts
|

Tubal anastomosis after tubal sterilization: a review

Abstract: There are few good-quality controlled studies in this area. Results of restoration of tubal patency seem to be comparable, regardless of the route of approach (laparotomy or laparoscopy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 39 publications
2
13
0
1
Order By: Relevance
“…In literature it is indicated that sterilization / reversal interval is indirectly proportional to over all pregnancy rate, 11 same is observed in our data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In literature it is indicated that sterilization / reversal interval is indirectly proportional to over all pregnancy rate, 11 same is observed in our data.…”
Section: Discussionsupporting
confidence: 91%
“…Deffieux and coworkers, have shown that more than 7 cm tubal length after surgery is an indicator for improved conception rate. 11 In our data 50% of the women conceived where the post surgery tube was more than 6 cm and it was statistically significant.…”
Section: Discussionsupporting
confidence: 45%
“…Pregnancy rates after tubal ligation reversal range from 31% to 88%. 51 Several factors affect the pregnancy rate after sterilization reversal. 52 Age is a significant factor, with a higher pregnancy rate for women younger than 36 years.…”
Section: Sterilization Reversalmentioning
confidence: 99%
“…112,121 Ectopic pregnancies following tubal reanastomosis with the abdominal approach are quoted as high as 12%, while only 7% for the laparoscopic approach. 122 Robotic-assisted tubal reanastomosis has proven to be particularly effective with a 97% pregnancy rate within the first 2 years for patients younger than 35 years 115 with a mean time to conception of 5.5 months postsurgery. 123 Interestingly, ectopic pregnancy removal with immediate segmental resection and robotic tubal reanastomosis in the setting of one viable fallopian tube to salvage natural fertility opportunity has been reported with a cumulative pregnancy rate of 63% and no ectopic pregnancies over 24 months of follow-up.…”
Section: Tubal Reanastomosismentioning
confidence: 99%